2015
DOI: 10.1248/bpb.b15-00199
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Effect of an Alternative Plasticizer, Diisopropyl Adipate, on a Contact Hypersensitivity Mouse Model: Link with Sensory Ion Channel TRPA1 Activation

Abstract: Due to health concerns about phthalate esters, the use of alternative plasticizers is being considered. Phthalate esters enhance skin sensitization to fluorescein isothiocyanate (FITC) in mouse models. We have demonstrated that phthalate esters stimulate transient receptor potential ankyrin 1 (TRPA1) cation channels expressed on sensory neurons. We also found a correlation between TRPA1 activation and the enhancing effect on FITC-induced contact hypersensitivity (CHS) when testing various types of phthalate es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…We have repeatedly demonstrated that 50% DBP enhanced the production of not only IL-4 but also IFN-γ. 9,10) In the present experiments, we showed that 2% DBP also enhanced the production of IL-4 as well as IFN-γ (Fig. 4).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…We have repeatedly demonstrated that 50% DBP enhanced the production of not only IL-4 but also IFN-γ. 9,10) In the present experiments, we showed that 2% DBP also enhanced the production of IL-4 as well as IFN-γ (Fig. 4).…”
Section: Discussionsupporting
confidence: 68%
“…We have demonstrated that DBP facilitated DC trafficking from skin to draining lymph nodes. 8,10) Twenty-four hours after epicutaneous treatment with FITC in the presence of 2% DBP, DBM or DBF, the number of FITC + CD11c + cells in brachial lymph nodes was increased as compared with the FITC treatment with acetone alone (Fig. 3).…”
Section: Effects Of Dbm and Dbf On Skin Sensitization To Fitc As Revmentioning
confidence: 95%
See 3 more Smart Citations